the Juazeiro das Candeias (Revista Internacional de Folkcomunicação, 2023)
The book Juazeiro das Candeias, by authors Elinaldo Meira and Maria Érica de Oliveira Lima, takes us to a timeless city, to the circuit of faith and pilgrimage of pilgrims, who year after year fill religious festivities in the municipality of Juazeiro do Norte. The book, the result of the author's post-doctoral work, is characterized by a collection of images, which, in addition to what the title proposes, takes us to the melting pot of cultural manifestations within the city of Juazeiro do Norte and surroundings.